Analisis Makna Kawā’ib dalam Al-Qur’an (Kajian Semantik Toshihiko Izutsu) - Monica, Salma; Dasuki, Akhmad; Faridatunnisa, Nor (Mashdar: Jurnal Studi Al-Qur'an dan Hadis, 2021)
The term kawā'ib is mentioned once in the Koran in surah al-Nabā 'verse 33. The term kawā'ib in al-Qur'an and the translation means plump girls. This "plump" translation gives the impression that the Koran uses a vulgar connotation. The purpose of this study is an effort to express the meaning of the term kawā'ib in the al-Qur'an with the semantic approach of Toshihiko Izutsu. This type of research includes library research. To obtain a more precise meaning, the data obtained were interpreted using descriptive analysis and analytic induction. The theory used is the semantics of Toshihiko Izutsu. The principle of Izutsu semantic analysis is to analyze the basic meaning, relational meaning, historical meaning, and weltanschauung. This study resulted in the conclusion that the basic meaning analysis, term kawā'ib in Arabic grammatical is taken from the root word "ka'b" which means something that rises or stands out. The term kawā'ib is the plural of the word "kā'ib" which means a virgin girl with plump breasts. Then the term kawā'ib has a relational meaning: synonyms and antonyms such as al-unṡā, al-nisā`, imra'ah, niswah, hūr, al-fatā, al-rijāl and al-dzakar. In the analysis of historical meaning, the term kawā'ib has the meaning of prominent breasts or plump and virgin breasts. And weltanschauung term "kawā'ib" is a figure of youth in each individual.